El proceso de iluminación en el cine de ficción ecuatoriano - Vaquero Dávila León, Marco Antonio (2018)
The study of this work is about light, its importance in the cinema and the way in which it has influence on the characters, the spectators and the people who work with it in film production. We will also analyze the lighting in the painting and how the cinematographers use these works as references for their work.